The predictive ability of the frequency of perfectionistic cognitions, self-oriented perfectionism, and socially prescribed perfectionism in relation to symptoms of burnout in youth rugby players - Hill, A. P.; Appleton, P. R. (Journal of Sports Sciences, 2011)
Perfectionism has been identified as an antecedent of athlete burnout. However, to date, researchers examining the relationship between perfectionism and athlete burnout have measured perfectionism at a trait level. The work of Flett and colleagues (Flett, Hewitt, Blankstein, & Gray, 1998) suggests that perfectionism can also be assessed in terms of individual differences in the frequency with which they experience perfectionistic cognitions. The aims of this study were to: (1)examine the relationship between the frequency of perfectionistic cognitions and symptoms of athlete burnout; and (2)determine whether the frequency of perfectionistic cognitions account for additional unique variance in symptoms of athlete burnout above the variance accounted for by self-oriented and socially prescribed dimensions of perfectionism. Two-hundred and two male rugby players (mean age 18.8 years, s = 2.9, range 16-24) were recruited from youth teams of professional and semi-professional rugby union clubs in the UK. Participants completed measures of trait perfectionism, frequency of perfectionistic cognitions, and symptoms of athlete burnout. The frequency of perfectionistic cognitions was positively related to all symptoms of athlete burnout and explained 3-4% unique variance in symptoms of athlete burnout after controlling for self-oriented and socially prescribed dimensions of perfectionism. Findings suggest that the frequency with which perfectionistic cognitions are experienced may also be an antecedent of athlete burnout. Perfectionistic cognitions should, therefore, be considered in both future models of the relationship between perfectionism and athlete burnout, as well as interventions aimed at reducing perfectionism fuelled burnout.